USE OF FLOYD ALGORITHM IN NETWORKS (Perner's Contacts, 2011)
This article deals with a use of Floyd algorithm for calculation of distances in a network, permeability of a network and the most reliable paths of a network.
Keywords: Floyd algorithm; distance matrix; distances in networks; permeability of a network; the most reliable paths of a network